Plant probiotic bacterial endophyte, alcaligenes faecalis, modulates plant growth and forskolin biosynthesis incoleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed G.; Vivek Babu, Chikkarasanahalli Shivegowda (Probiotics and Antimicrobial Proteins, 2020)
Coleus forskohliiis an herb, well-known for its medicinal compound forskolin present in its roots, with wide range of pharmaceutical applications. Here, we report, for the first time, the role of plant-probiotic bacterial endophytes ofC. forskohlii, CFLB1 and CFRB1, isolated from leaf and root, which regulate plant growth andin plantforskolin content. Native bacterial endophyte, CFRB1 (Alcaligenes faecalis), significantly modulates primary plant productivity and forskolin content under pot and field conditions. Under field conditions, CFRB1 endophyte application significantly enhanced photosynthetic pigments and reduced the severity of root-knot and root rot diseases. Expression analyses of functional genes involved in the forskolin biosynthesis inC. forskohliiplants treated with CFRB1 endophyte under field conditions revealed differential upregulation of fourC. forskohliiditerpene synthases (CfTPSs),CfTPS1,CfTPS2,CfTPS3andCfTPS4, along with cytochrome P450 (CfCYP76AH15) and acyltransferase (CfACT1-8) genes. CFRB1 treatment reduced the severity of nematode infection and root rot inC. forskohliiplants by 81 and 78%, respectively. Overall, we demonstrate that cross-talk of plant-endophyte interaction inC. forskohliiis beneficial, leading to enhanced forskolin content through modulation of forskolin biosynthetic pathway genes along with increased plant yield and reduced disease incidence. Thus, endophytic isolate,A. faecalis(CFRB1), could be deployed as a novel bio-stimulant for enhancingin plantaforskolin content during cultivation ofC. forskohlii.
Keywords: Alcaligenes faecalis; CfACT1-8; CfCYP76AH15; CfTPSs; Coleus forskohlii; Forskolin; Plant-probiotic bacterial endophyte